Inventory of Porifera Species in the Northern and Southern Parts of Tidung Kecil Island, Kepulauan Seribu - Canakhya, Rayinda Al Ganiya; Sukardi, Ratnaduhita Aprilia Putri; Aizah, Pratiwi Nur (Dept. Marine Science, 2026)
This study aims to identify the types of Porifera found in the northern and southern waters of Tidung Kecil Island, Kepulauan Seribu. A descriptive–exploratory approach was used through a free-roaming survey along a 150 m transect from the shoreline at each site. Samples were collected purposively based on substrate characteristics and environmental conditions favorable for sponge growth. Each specimen was identified through macroscopic observations of body form, color, and surface texture, and microscopic examination of spicule types using permanent slides. The result recorded six species belonging to the class Demospongiae: Aplysina aerophoba, Clathria prolifera, Siphonodictyon infestum, Spheciospongia inconstans, Cliona viridis, and Spongilla lacustris. Most species were found in the southern area dominated by hard sand and coral rubble substrates, while A. aerophoba and S. lacustris were observed in the northern area with finer sand substrates. The observed spicules were predominantly monoaxonic style forms, while C. prolifera exhibited a combination of oxeas and style, and A. aerophoba lacked spicules entirely. These findings indicate that morphological and spicular variations among porifera are closely related to local environmental conditions and substrate types, highlighting the high diversity of sponges in the shallow tropical waters of the Kepulauan Seribu.